Regulatory Consistency in Tax Crime Enforcement: Judicial Decisions, Financial Sanctions, and Taxpayer Compliance - Nofryanti; Tatariyanto, Firman (Indonesian Financial Review, 2025)
This study examines judicial consistency in tax crime enforcement as a determinant of regulatory credibility and taxpayer compliance in Indonesia. Despite the central role of criminal sanctions as an ultimum remedium, variations in judicial decisions may weaken enforcement signals and reduce deterrence. Using qualitative content analysis on 22 Supreme Court decisions (2020–2023), this study evaluates sentencing patterns, proportionality of financial penalties, and their alignment with statutory provisions. The findings reveal substantial disparities in fines and imprisonment, particularly under Article 39, where sanctions frequently fall below statutory multipliers. In contrast, Article 39A demonstrates relatively strong consistency. These inconsistencies reduce predictability, weaken deterrence, and potentially undermine voluntary compliance. This study contributes to the literature by integrating legal enforcement analysis with financial regulation theory, highlighting the importance of judicial coherence in strengthening regulatory credibility and sustaining public finance governance.